Antithrombin Activity of Intact Human Platelets - Watanabe, Kiyoake; Chao, Francis C; Tullis, James L (Thrombosis and Haemostasis, 1975)
Antithrombin activity has been identified in intact washed human platelets. An apparent activity was demonstrated at platelet concentrations above 0.31 × 109/ml, when platelet suspensions were incubated with 2.0 NIH units/ml of thrombin. Neither red cells nor white cells revealed antithrombin activity. No significant loss of the platelet antithrombin activity was observed after ten successive washings or after treatment of platelets with antibodies to antithrombin III or α2-macroglobulin. Almost the same amount of antithrombin activity as normal platelets was demonstrated in the platelets from an afibrinogenemic patient. Pre-treatment of platelets with trypsin, papain, and neuroaminidase reduced the activity significantly, whereas lipase was without effect. The platelet antithrombin reacted with thrombin in less than 3 seconds, and this rapid reaction of platelet antithrombin was different from that of plasma antithrombin III or fibrinogen. The thrombin-like clotting activity of ancrod was inhibited by fibrinogen but not platelets. Also, unlike plasma antithrombin III or fibrinogen, brief exposure to heat (56° C or 60° C) reduced considerable amounts of platelet antithrombin activity. These results suggest that platelets possess a specific antithrombin with different characteristics from other known antithrombins.